Regular Egg-Positioning by an Aeshnid Species (Odonata, Aeshnidae) with Comments on its Phylogenetic Value - Matushkina, N.A. (Вестник зоологии, 2007)
Prolarvae and first-instar larvae of an aeshnid anisopteran, probably Aeshna sp. or Anaciaeschna isoceles, were reared from an endophytic egg-clutch with eggs positioned in line and zigzag orders in stems and flowerstems of Myriophyllum spicatum in central Ukraine. Descriptions of the prolarva and the first-instar larva, the distance between neighbouring eggs in the clutch, as well as discussion on evolution of the endophytic egg-laying behaviour in Odonata, are provided. В стеблях и цветоносах Myriophyllum spicatum были обнаружены кладки стрекоз, содержащие расположенные линейно и зигзагом яйца. Из них в условиях лаборатории получены предличинки и личинки первого возраста стрекоз из семейства Aeshnidae (Anisoptera), возможно относящиеся к виду Anaciaeschna isoceles или роду Aeshna sp. В работе приведены описания морфологии яйца, личиночных стадий и кладок. Кратко обсуждается эволюция эндофитной откладки яиц у стрекоз.